Carvedilol-mediated antioxidant protection against doxorubicin-induced cardiac mitochondrial toxicity - Oliveira, Paulo J. (2004)
The cardiotoxicity associated with doxorubicin (DOX) therapy limits the total cumulative dose and therapeutic success of active anticancer chemotherapy. Cardiac mitochondria are implicated as primary targets for DOX toxicity, which is believed to be mediated by the generation of highly reactive free radical species of oxygen from complex I of the mitochondrial electron transport chain. The objective of this study was to determine if the protection demonstrated by carvedilol (CV), a [beta]-adrenergic receptor antagonist with strong antioxidant properties, against DOX-induced mitochondrial-mediated cardiomyopathy [Toxicol. Appl. Pharmacol. 185 (2002) 218] is attributable to its antioxidant properties or its [beta]-adrenergic receptor antagonism. Our results confirm that DOX induces oxidative stress, mitochondrial dysfunction, and histopathological lesions in the cardiac tissue, all of which are inhibited by carvedilol. In contrast, atenolol (AT), a [beta]-adrenergic receptor antagonist lacking antioxidant properties, preserved phosphate energy charge but failed to protect against any of the indexes of DOX-induced oxidative mitochondrial toxicity. We therefore conclude that the cardioprotective effects of carvedilol against DOX-induced mitochondrial cardiotoxicity are due to its inherent antioxidant activity and not to its [beta]-adrenergic receptor antagonism.